THE HEIRS TO THE GERMAN IMPERIAL THRONE AND THEIR ATTITUDE TO NATIONAL SOCIALISM (Південний архів (історичні науки), 2023)
The purpose of the article is to highlight the attitude of the direct imperial descendant, Crown Prince William III, to National Socialism, his monarchical hopes and their consequences. The methodological is based on the principles of historicism, systematicity, objectivity, and scientificity, with the help of which the content of socio-political processes and phenomena is revealed. General scientific methods are widely used in the article: analysis, synthesis, generalization, specification. Among the special scientific methods: historical, historical-systemic, specific-historical. The relevance of the research lies in the fact that on December 7, 2022, an attempted coup d’état in Germany with the aim of restoring the monarchy was exposed. Georg Friedrich, Prince of Prussia, an imperial descendant, was to head the newly created monarchy in Germany. Since 2014, the Hohenzollern family and the governments of the federal states of Berlin and Brandenburg have been in talks to return the property in accordance with the 1994 law. However, the 1994 law provides for exceptions: no return occurs if the testator provided "significant support" to the National Socialist regime. In the case of the Hohenzollern, the debate centered on the attitude of Crown Prince Wilhelm (1882–1951), head of the family at the time of Germany’s defeat in 1945, to National Socialism. So, this topic is relevant in today’s realities, that is why it is important to study and research this issue. Research results. Highlighting the activities of Crown Prince Wilhelm, a descendant of the Hohenzollern imperial dynasty, regarding the restoration of the monarchy in Germany with the support of the National Socialists who came to power in Germany. Based on the sources, the possible connections of the National Socialists with the imperial family, their causes and consequences are analyzed. Conclusions. During the competition for political influence in the country, Crown Prince Wilhelm played a small but important role. The heir to the throne placed his bets on the right because he saw in them a chance to restore the monarchy. In the presidential elections, he also nominated his candidacy, but it failed, and then Wilhelm announced his support for Hitler. But in the end, the crown prince’s hopes for cooperation with right-wing nationalists remained unfulfilled, and in 1936 Wilhelm stopped his political activities. During World War II, he did not play a significant role, and in 1951 he died in Gechingen in southwestern Germany. However, his public support as a representative of the former monarchy of the Nazi regime made a depressing impression on all those who tried to resist Nazism and popularized Nazism in Germany among the neophytes.
Keywords: emperor, crown prince, monarchy, power, president, National Socialism, National Socialist German Workers’ Party, German National People’s Party, Potsdam Day